The Relationship Between Corporate Governance and Earnings Management----Evidence from Chinese Listed Non-family and Family firms - Zong, Bingbing (2020)
Since many scandals were released, earnings management has become a popular topic among researchers and stakeholders. To supervise manager's behavior and guide company operations, effective corporate governance is set. By utilizing Chinese all listed companies over the year 2015-2019 as research objectives, this paper empirically invests distinct impacts of the corporate governance on the earnings management among non-family and family firms from two aspects: the board of directors and the ownership structure. All companies are divided into non-family firms and family firms to discover detailed relationship. The results show that the more independent directors, the less likely the manager to manipulate earnings and this regulatory role is more significant in family firms. However, this paper cannot demonstrate how the board size affects earnings management, mainly because compared with other factors, the effect of this factor is not apparent. Besides, the CEO duality might avoid managers manipulating earnings in non-family firms while the connection is not obvious in family firms. Then, in terms of the ownership structure, the concentrated ownership will cause executives to manage profits more often in non-family firms while the concentrated ownership will restrain this behavior in family firms. Additionally, institutional investors play an important role in increasing the quality of earnings among non-family and family firms and this function is more effective in non-family firms.